The education of the public library in Costa Rica: a contribution to the discussion - Rodríguez Chaves, Olga (2002)
This paper analyzes the schooling of the public library in Costa Rica, as well as the functioning and management of these units within society. A description of the main statements that protect the research, in addition mentions evolutionary aspects and transformers of the library system at national and regional level. Expose chronologically the typologies of public libraries, to subsequently refer the pedagogical work of these institutions.